Implementation of LDG method for 3D unstructured meshes - Sequeira Chavarría, Filander A. (2012)
This paper describes an implementation of the Local Discontinuous Galerkin method (LDG) applied to elliptic problems in 3D. The implementation of the major operators is discussed. In particular the use of higher-order approximations and unstructured meshes. Efficient data structures that allow fast assembly of the linear system in the mixed formulation are described in detail.